A Premature Rupture of Membranes in Pregnancies with Abnormal Fetal Presentation - Putri, Alya Fatma; Amani, Patwa (JIKES : Jurnal Ilmu Kesehatan, 2026)
Premature rupture of membranes (PROM) is a significant obstetric complication that can lead to increased maternal and neonatal morbidity. This study aimed to determine the relationship between fetal malpresentation and PROM. Using an observational analytic method with a cross-sectional design, data were collected from medical records of 63 mothers who delivered at RSUD Dr. H. Abdul Moeloek in 2024. The results showed that 39.7% of respondents experienced fetal malpresentation and 47.6% had PROM. Among those with malpresentation, 64,0% experienced PROM. Statistical analysis using the Chi-square test revealed a significant association (p = 0.035) between fetal malpresentation and PROM. These findings suggest that malpresentation increases the risk of PROM. The study highlights the importance of early detection and management of fetal malpresentation to reduce PROM-related complications.